XPS surface analysis of ceria-based materials: Experimental methods and considerations - Mark A. Isaacs; Charalampos Drivas; Roxy Lee; Robert Palgrave; Christopher M.A. Parlett; David J. Morgan (Applied Surface Science Advances, 2023)
X-ray photoelectron spectroscopy (XPS) analysis of cerium is ubiquitous amongst the catalytic and materials literature however errors in experimental procedure and data analysis are often easily proliferated. In this work we focus on the best practice for experimental construction when approaching the task of understanding chemical environments in cerium-based materials by XPS.